Usefulness of RT-PCR in Follow Up of a Case with Acute Lymphoblastic Leukemia with 1;19 Translocation - OKAMOTO, Norihiko; KOJIMA, Kyouko; OHARA, Akira; NAKAZAWA, Sinnpei; SAWAI, Kiyoshi; HAYASHI, Yasuhide; MIZUTANI, Syuki; TUUKIMOTO, Itirou; SUZUKI, Toshio; SAWA, Fumihiro (The Japanese Journal of Pediatric Hematology, 1993)
A 4-year-old girl was diagnosed in June 1990 as having acute lymphoblastic leukemia (ALL) with (1;19) translocation. Complete remission was obtained with TCCSG L84-12 intermediate risk protocol. Seven months after reinduction therapy, 50% of bone marrow cells showed blast-like morphology, with CD 10, 19, 20, HLA-DR antigen expression. In order to clarify whether the blast-like cells represent leukemic relapse or not, E2A-PBX1 chimeric mRNA was analyzed with RT-PCR. It showed only leukemic cell with (1;19) translocation. E2A-PBX1 transcript, which was expressed in the initial presentation sample, was not detected in those blast-like cells. Subsequently the patient was diagnosed as being in complete remisson. In this case, the continuous complete remission has been confirmed by the negativity of a serial E2A-PBX1 expression during treatment period.